Configuración Software de la directividad de arrays lineales - Martínez Serrano, Antonio A; Ortega Valle, Alfonso D.; Munilla-Fajardo, Jorge (My University, 2015)
A line array can be defined as a column of loudspeakers that is designed so that these work together to achieve a higher directivity. This paper presents an application that enables a user to rotate the wavefront of uniform line arrays. Theoretical background and details of the implementation are provided. The validity of the application is tested with measurements of the directivity that are also compared with simulations.
Keywords: Telecomunicaciones; Array altavoces; Directividad; Software; Inteligibilidad; Array lineal